Dual antibiotic prevention bundle is associated with decreased surgical site infections. Issue 9 (29th July 2020) - Kuznicki, Michelle; Mallen, Adrianne; McClung, Emily Clair; Robertson, Sharon E; Todd, Sarah; Boulware, David; Martin, Stacy; Quilitz, Rod; Vargas, Roberto J; Apte, Sachin M
Abstract : Background: Gynecologic oncology surgery is associated with a wide variation in surgical site infection risk. The optimal method for infection prevention in this heterogeneous population remains uncertain. Study Design: A retrospective cohort study was performed to compare surgical site infection rates for patients undergoing hysterectomy over a 1-year period surrounding the implementation of an institutional infection prevention bundle. The bundle comprised pre-operative, intra-operative, and post-operative interventions including a dual-agent antibiotic surgical prophylaxis with cefazolin and metronidazole. Cohorts consisted of patients undergoing surgery during the 6 months prior to this intervention (pre-bundle) versus those undergoing surgery during the 6 months following the intervention (post-bundle). Secondary outcomes included length of stay, readmission rates, compliance measures, and infection microbiology. Data were compared with pre-specified one-sided exact test, Chi-square test, Fisher's exact test, or Kruskal–Wallis test as appropriate. Results: A total of 358 patients were included (178 PRE, 180 POST). Median age was 58 (range 23–90) years. The post-bundle cohort had a 58% reduction in surgical site infection rate, 3.3% POST vs 7.9% PRE (−4.5%, 95% CI −9.3% to −0.2%, p=0.049) as well as reductions in organ space infection, 0.6% POST vs 4.5% PRE (−3.9%, 95% CI −7.2% to −0.7%, p=0.019), and readmission rates, 2.2% POST vs 6.7% PRE (−4.5%, 95% CI −8.7% to −0.2%, p=0.04). Gram-positive, Gram-negative, and anaerobic bacteria were all prevalent in surgical site infection cultures. There were no monomicrobial infections in post-cohort cultures (0% POST vs 58% PRE, p=0.04). No infections contained methicillin-resistant Staphylococcus aureus . Conclusion: Implementation of a dual antibiotic infection prevention bundle was associated with a 58% reduction in surgical site infection rate after hysterectomy in a surgically diverse gynecologic oncology practice.